A urea-based dispersant suitable for a variety of nanomaterials and a preparation method thereof
Patent Information
- Application Number
- CN202611461530.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]针对现有技术中纳米材料在油相介质中易团聚、分散稳定性差,以及现有表面化学改性工艺繁琐、条件苛刻、难以工业化生产的问题,本发明提供一种适用于多种纳米材料的脲基分散剂及其制备方法
[0026](1)制备工艺简单、绿色环保:仅通过一步加成反应即可在基础油中原位生成脲基分散组分,无需对纳米材料进行复杂的表面化学修饰,避免了传统方法中大量有机溶剂的使用及繁琐的后处理过程,成本低廉,操作简便,易于工业化生产;
Smart Images

Figure CN122978006A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials, specifically to the field of nanomaterial dispersion, and more specifically to a urea-based dispersant suitable for nanomaterials and its preparation method. Background Technology
[0002] In recent years, nanomaterials have exhibited unique interfacial properties due to their special size effect, resulting in significantly improved electrical and thermal conductivity. They have found wide applications in fields such as photocatalysis, biomedicine, and friction lubrication. In the field of friction lubrication, nanomaterials can be used as lubricating additives to improve the lubrication performance of base oils by forming a protective film on the friction surface or filling micro-defects on the friction pair surface.
[0003] However, due to their high surface energy, nanomaterials are prone to agglomeration in liquid media. Agglomerated nanomaterials not only fail to exert their intended friction-reducing and wear-resistant effects, but may also act as hard abrasive particles, exacerbating abrasive wear, leading to an increase in the system's friction coefficient and wear, severely restricting the further development of nano-lubrication technology.
[0004] To address the core issue of poor dispersion stability of nanomaterials in base oils, researchers both domestically and internationally have primarily employed surface chemical modification techniques, including surfactant physical coating and polymer grafting modification. For instance, Zhang et al. modified black phosphorus nanosheets with dodecyl mercaptan and added them to polyurea grease at different concentrations. The results showed that when the modified nanosheets were added at 2 wt%, the friction coefficient decreased by 39% compared to the base oil, and the wear volume decreased by 16.3% (B. Zhang, et al., Tribology International, 216(2026), 111606). Ding et al. modified silica nanoparticles with amino groups and found that when the addition amount was 5 wt%, compared to unmodified nanoparticles, the friction coefficient decreased by 38%, and the time required to reach the stable friction stage was shortened by 49% (M. Ding, et al., Ceramics International, 44(2018), 14901-14906). While the aforementioned modification methods have improved the dispersibility and tribological properties of nanomaterials to some extent, they typically suffer from cumbersome processes, demanding reaction conditions, and low yields, making it difficult to meet the needs of large-scale industrial production. Furthermore, existing modification processes often require the use of large amounts of organic solvents or toxic raw materials, posing potential hazards to operators and the environment.
[0005] Therefore, how to provide a dispersant that is simple to prepare, environmentally friendly, easy to industrialize, and capable of enabling the long-term stable dispersion of various nanomaterials in an oil-phase medium is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] To address the problems of easy agglomeration and poor dispersion stability of nanomaterials in oil-phase media in existing technologies, as well as the cumbersome, demanding, and difficult-to-industrialize surface chemical modification processes, this invention provides a urea-based dispersant suitable for various nanomaterials and its preparation method. This invention generates urea molecules with excellent oil solubility as a dispersing component through in-situ reaction in base oil, achieving long-term stable dispersion of various nanomaterials in oil-phase media without the need for complex surface chemical modification.
[0007] In a first aspect, the present invention provides a urea compound having the structural formula shown in formula (Ⅰ):
[0008] .
[0009] Secondly, the present invention provides a method for preparing a urea-based dispersion, comprising the following steps:
[0010] (1) Add toluene-2,4-diisocyanate to the first part of the base oil, stir and disperse evenly to obtain an isocyanate base oil mixture;
[0011] (2) Add di-n-octylamine to the second part of the base oil, stir and disperse evenly to obtain an amine base oil mixture; the molar ratio of toluene-2,4-diisocyanate to di-n-octylamine is 1:1.8~2.2;
[0012] (3) The amine base oil mixture is added dropwise to the isocyanate base oil mixture. Under stirring, the mixture is heated to 150-200°C and kept at a constant temperature for 30-60 min to allow toluene-2,4-diisocyanate and di-n-octylamine to undergo an in-situ addition reaction in the base oil to generate the urea compound shown in formula (I). After the reaction is completed, the resulting reaction system is cooled to 20-25°C to obtain the urea dispersion.
[0013] The mass percentage of urea molecules in the obtained urea-based dispersion is 2-10 wt%.
[0014] The base oil is any one of polyalphaolefin, pentaerythritol tetra(2-ethylhexanoate), or industrial white oil.
[0015] This invention utilizes an in-situ reaction of toluene-2,4-diisocyanate and di-n-octylamine in a base oil to generate a novel urea molecule as shown in formula (I). Traditional urea molecules with thickening properties are referenced. Figure 1At a concentration of 5 wt%, the samples were white semi-solid or solid. In contrast, the urea compounds prepared in this invention exhibited virtually no thickening effect in base oils and possessed good oil solubility. Even when the urea molecule content in the oil phase reached 10 wt%, the dispersion system remained a pale yellow and transparent state. Figure 1 In c and g (Example 5), no white flocculent precipitate will appear; the appearance of the 5 wt% concentration sample is as follows: Figure 1 As shown in examples a and e (Example 4). Figure 2 As shown, in preparing the dispersion of nanomaterials, simply adding an appropriate amount of nanomaterials to a pre-prepared urea-based dispersion, followed by stirring and ultrasonic treatment, yields a stable dispersion of nanomaterials. This dispersion can remain stable at room temperature for more than 10 days, with samples exhibiting superior dispersion stability able to remain stable for over 100 days without significant sedimentation or stratification, demonstrating excellent potential for industrial application. Furthermore, if sedimentation occurs in the nanomaterial dispersion after prolonged storage, repeated ultrasonic treatment is sufficient to restore it to a uniform dispersion state for continued use, further enhancing its practical application value.
[0016] Preferably, the base oil is either polyalphaolefin (PAO8) or pentaerythritol tetra(2-ethylhexanoate) ester (PEB8).
[0017] Preferably, the amount of toluene-2,4-diisocyanate is 0.66 to 1.66 wt% of the total mass of the reaction system, and the amount of di-n-octylamine is 1.33 to 3.33 wt% of the total mass of the reaction system.
[0018] Preferably, the stirring and dispersion temperature in step (1) is 40~50℃ and the time is 10 min; the stirring and dispersion temperature in step (2) is 40℃ and the time is 10 min; and in step (3), the temperature is raised to 170~180℃ and the reaction is kept at a constant temperature for 60 min.
[0019] Preferably, the mass percentage of urea molecules in the obtained urea-based dispersion is 2-10 wt%, more preferably 2-5 wt%, and even more preferably 2 wt%.
[0020] Secondly, the present invention provides a urea-based dispersion prepared by the above-described preparation method. When the content of the urea-based compound is not higher than 10 wt%, the urea-based dispersion is colorless or pale yellow and transparent, and no flocculent precipitate is observed.
[0021] Thirdly, the present invention provides a nanomaterial dispersion comprising the above-mentioned urea-based dispersion and nanomaterials dispersed in the urea-based dispersion. In application, the urea-based dispersion of the present invention primarily disperses the nanomaterials through urea molecules uniformly distributed in the oil phase. This dispersion effect may be related to van der Waals forces and hydrogen bonding between the nanomaterials and the urea-based compound. The long-chain alkyl groups contained in the urea molecules impart good compatibility with the base oil. Figure 2 The aggregation of nanomaterials is suppressed through steric hindrance and interfacial interactions. Because the urea molecule exhibits only weak intermolecular interactions in the oil phase, the resulting system maintains good fluidity and can be used as a novel cutting fluid or lubricating dispersion system.
[0022] Preferably, the nanomaterial is at least one of carbon nanotubes, graphene, molybdenum disulfide (MoS2) or hexagonal boron nitride (h-BN), and its particle size or sheet size is not greater than 1 μm; the amount of the nanomaterial added accounts for 0.5 to 1 wt% of the total mass of the nanomaterial dispersion.
[0023] Fourthly, the present invention provides a method for preparing the above-mentioned nanomaterial dispersion: the nanomaterial is added to the urea-based dispersion, and the mixture is alternately stirred and ultrasonically treated to uniformly disperse the nanomaterial in the urea-based dispersion, thereby obtaining the nanomaterial dispersion.
[0024] Fifthly, the present invention provides the application of the above-mentioned nanomaterial dispersion as a lubricating oil additive dispersion system or a cutting fluid.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0026] (1) The preparation process is simple and environmentally friendly: urea-based dispersion components can be generated in situ in base oil through a one-step addition reaction. There is no need to perform complex surface chemical modification on nanomaterials, avoiding the use of a large amount of organic solvents and cumbersome post-processing in traditional methods. It is low in cost, easy to operate, and easy to industrialize.
[0027] (2) The obtained urea-based dispersion is colorless or pale yellow and transparent when the urea molecule content is not higher than 10 wt%, and there is no flocculent precipitation. Unlike traditional urea thickeners, it does not form white flocculent precipitation, which is beneficial for subsequent observation of the dispersion state of nanomaterials.
[0028] (3) Excellent dispersion stability of nanomaterial dispersions: Various nanomaterials (such as carbon nanotubes, hexagonal boron nitride, and molybdenum disulfide) can be stably dispersed for more than 10 days at 20~25℃ without significant sedimentation or stratification. Among them, the samples with better dispersion stability can be stably stored for more than 100 days. Furthermore, after sedimentation occurs in the dispersion after long-term storage, it can be restored to a uniform dispersion state and continued to be used after ultrasonic treatment again.
[0029] (4) Wide range of applications: The urea-based dispersion is soluble in a variety of base oils and can effectively assist in the stable dispersion of various nanomaterials such as carbon nanotubes, graphene, molybdenum disulfide, and hexagonal boron nitride;
[0030] (5) The urea-based dispersion can maintain the structural integrity of the nanomaterials in a better way during the auxiliary dispersion process, which helps the nanomaterials to play a role in reducing friction and anti-wear in the lubrication system. The obtained nanomaterial dispersion can be used as a lubricating oil additive dispersion system or cutting fluid, and has good engineering application prospects. Attached Figure Description
[0031] Figure 1 The images show the appearance of the urea-based dispersion and conventional urea-based materials provided in the embodiments of the present invention; wherein (a) and (e) are 5 wt% urea-based dispersions prepared with PAO8 as the base oil (Example 4), (b) and (f) are 5 wt% urea-based dispersions prepared with PEB8 as the base oil, (c) and (g) are 10 wt% urea-based dispersions prepared with PAO8 as the base oil (Example 5), and (d) and (h) are conventional 5 wt% polyurea samples; (a), (b), (c), and (d) are side views, and (e), (f), (g), and (h) are top views;
[0032] Figure 2 This is a schematic diagram of the synthesis of the urea-based dispersion of the present invention and the reaction equation; wherein (a) is a schematic diagram of the synthesis process of the urea-based dispersion, and (b) is the chemical reaction equation for the reaction of toluene-2,4-diisocyanate and di-n-octylamine to generate urea molecules.
[0033] Figure 3 The images are of the appearance of the samples obtained in Examples 1-3 and Comparative Examples 1-2 after being left to stand at 20-25°C for 1 day, 2 days, 3 days, 5 days, 7 days and 10 days, respectively.
[0034] Figure 4 These are appearance photos taken after Example 1 and Example 2 were left to stand at 20~25°C for 100 days.
[0035] Figure 5 Infrared spectra of toluene-2,4-diisocyanate (TDI), di-n-octylamine, PAO8 base oil, and 5% urea / PAO8 dispersion.
[0036] Figure 6 The results of friction tests on the PAO8 base oil and Example 1 were obtained using an SRV friction testing machine. The experimental conditions were: load 100 N, temperature 25 °C, frequency 25 Hz, and stroke 1 mm. Detailed Implementation
[0037] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, unless otherwise specified, the following embodiments and features described therein can be combined with each other.
[0038] like Figure 2 As shown, in this invention, toluene-2,4-diisocyanate (TDI) and di-n-octylamine are first dissolved in base oil, and then the amine base oil mixture is added dropwise to the isocyanate base oil mixture. The mixture is heated to allow the two to react in situ in the base oil to generate urea molecules as shown in formula (I) (characterization image see...). Figure 5 After cooling, a urea-based dispersion is obtained; then, the nanomaterial is directly added to the urea-based dispersion, and after alternating stirring and sonication, a nanomaterial dispersion is obtained.
[0039] Figure 5 The TDI spectrum is located at 2270 cm⁻¹ -1 The characteristic peak belongs to the in-plane stretching vibration of -NCO, located at 1130 cm⁻¹ in the di-n-octylamine spectrum. -1 The characteristic peak at [location] belongs to the asymmetric stretching vibration peak of CNC. However, in the 5 wt% urea / PAO8 sample, both of these characteristic peaks disappeared, indicating that TDI and di-n-octylamine in the substrate had completely reacted and been exhausted. Meanwhile, the product [value] at approximately 1640 cm⁻¹ -1 and 1540 cm -1 The presence of urea carbonyl stretching vibration and characteristic absorption of amide II band indicates that the isocyanate group of TDI undergoes an addition reaction with the secondary amino group of di-n-octylamine to form a urea bond.
[0040]
[0041] Example 1: 2 wt% urea + 1 wt% multi-walled carbon nanotube / PAO8 dispersion
[0042] a. Preparation of urea-based dispersion: Weigh 0.106 g of toluene-2,4-diisocyanate (TDI) and add it dropwise to 9.4 g of PAO8 base oil. Stir magnetically at 45°C for 10 min to obtain a uniformly dispersed isocyanate base oil mixture. Separately weigh 0.294 g of di-n-octylamine (molar ratio of TDI to di-n-octylamine is 1:2) and add it to 10.0 g of PAO8. Stir at 40°C for 10 min to ensure uniform dispersion, obtaining an amine base oil mixture. Subsequently, slowly add the amine base oil mixture dropwise to the isocyanate base oil mixture. Under stirring, heat the mixture to 170°C and maintain the temperature for 60 min to allow TDI and di-n-octylamine to react in situ in the base oil to generate urea molecules. After the reaction, cool the system to 20-25°C to obtain a colorless or pale yellow, transparent to translucent urea-based dispersion, wherein the mass percentage of urea molecules is 2 wt%.
[0043] b. Preparation of nanomaterial dispersion: Weigh 0.20 g of multi-walled carbon nanotubes (approximately 50-60 nm in diameter), add them to the above urea-based dispersion, stir for 10 min, sonicate for 10 min, stir again for 10 min, and repeat sonication for 10 min to obtain a uniformly dispersed nanomaterial dispersion, wherein the content of multi-walled carbon nanotubes is 1 wt%. Observe the dispersion state of the sample after standing. The results after 10 days of dispersion are as follows: Figure 3 As shown, the results after 100 days are as follows: Figure 4 As shown.
[0044] Example 2: 2 wt% urea + 1 wt% hexagonal boron nitride / PEB8 dispersion
[0045] a. Preparation of urea-based dispersion: Weigh 0.106 g of toluene-2,4-diisocyanate (TDI) and add it dropwise to 9.4 g of PEB8 base oil. Stir magnetically at 45°C for 10 min to obtain a uniformly dispersed isocyanate base oil mixture. Separately weigh 0.294 g of di-n-octylamine (molar ratio of TDI to di-n-octylamine is 1:2) and add it to 10.0 g of PEB8. Stir at 40°C for 10 min to ensure uniform dispersion, obtaining an amine base oil mixture. Subsequently, slowly add the amine base oil mixture dropwise to the isocyanate base oil mixture. Under stirring, heat the mixture to 180°C and maintain the temperature for 60 min to allow TDI and di-n-octylamine to react in situ in the base oil to generate urea molecules. After the reaction, cool the system to 20-25°C to obtain a colorless or pale yellow, transparent to translucent urea-based dispersion, wherein the mass percentage of urea molecules is 2 wt%.
[0046] b. Preparation of nanomaterial dispersion: Weigh 0.20 g of hexagonal boron nitride nanosheets (approximately 100-200 nm in size), add them to the above urea-based dispersion, stir for 10 min, sonicate for 10 min, stir again for 10 min, and repeat sonication for 10 min to obtain a uniformly dispersed nanomaterial dispersion, wherein the content of hexagonal boron nitride is 1 wt%. The results after 10 days of dispersion are as follows. Figure 3 As shown, the results after 100 days are as follows: Figure 4 As shown.
[0047] Example 3: 2 wt% urea + 0.5 wt% molybdenum disulfide / PEB8 dispersion
[0048] a. Preparation of urea-based dispersion: The preparation steps of the urea-based dispersion are the same as step a in Example 2, resulting in a urea-based dispersion with a urea molecule content of 2 wt%.
[0049] b. Preparation of nanomaterial dispersion: Weigh 0.10 g of molybdenum disulfide nanoparticles (approximately 300 nm in size), add them to the above urea-based dispersion, stir for 10 min, sonicate for 10 min, stir again for 10 min, and repeat sonication for 10 min to obtain a uniformly dispersed nanomaterial dispersion, wherein the molybdenum disulfide content is 0.5 wt%. The dispersion results are as follows: Figure 3 As shown.
[0050] Example 4: 5 wt% urea dispersion / PAO8
[0051] a. Weigh 0.265 g of toluene-2,4-diisocyanate (TDI), add it to 10.0 g of PAO8 base oil, and stir at 40°C for 20 min to uniformly disperse the TDI and obtain an isocyanate base oil mixture.
[0052] b. Weigh 0.734 g of di-n-octylamine and add it to 9.0 g of PAO8 base oil. Heat the mixture to 40 °C and stir for 20 min to uniformly disperse the di-n-octylamine, obtaining an amine base oil mixture. Under continuous stirring, slowly add the amine base oil mixture dropwise to the isocyanate base oil mixture. After the addition is complete, gradually heat the mixture to 150 °C and maintain this temperature for 30 min to allow TDI and di-n-octylamine to react in situ in the PAO8 base oil to generate urea molecules. After the reaction is complete, allow the system to cool naturally to 20–25 °C to obtain a urea-based dispersion with a mass fraction of 5 wt%.
[0053] The obtained urea-based dispersion was colorless and transparent, with no obvious flocculent precipitation observed, and the system exhibited good fluidity. Side and top view photographs of the obtained sample are shown below. Figure 1 As shown in Figures a and e. Figure 5The images show the infrared spectra of toluene-2,4-diisocyanate (TDI), di-n-octylamine, PAO8 base oil, and the prepared 5wt% urea / PAO8. The TDI spectrum is located at 2270 cm⁻¹. -1 The characteristic peak belongs to the in-plane stretching vibration of -NCO, located at 1130 cm⁻¹ in the di-n-octylamine spectrum. -1 The peak at [location] corresponds to the asymmetric stretching vibration peak of CNC. However, in the 5 wt% urea dispersion / PAO8 sample, both characteristic peaks disappeared, indicating that TDI and di-n-octylamine in the substrate had completely reacted and been exhausted. Meanwhile, the product [peak] at approximately 1640 cm⁻¹ -1 and 1540 cm -1 The presence of urea carbonyl stretching vibration and characteristic absorption of amide II band indicates that the isocyanate group of TDI undergoes an addition reaction with the secondary amino group of di-n-octylamine to form a urea bond.
[0054] Example 5: 10 wt% urea dispersion / PAO8
[0055] a. Weigh 0.530 g of toluene-2,4-diisocyanate (TDI), add it to 10.0 g of PAO8 base oil, and stir at 40°C for 20 min to uniformly disperse the TDI and obtain the isocyanate base oil mixture.
[0056] b. Weigh 1.467 g of di-n-octylamine and add it to 8.0 g of PAO8 base oil. Heat the mixture to 40°C and stir for 20 min to ensure uniform dispersion of the di-n-octylamine, thus obtaining an amine base oil mixture. The molar ratio of TDI to di-n-octylamine is approximately 1:2.
[0057] c. Under continuous stirring, the amine base oil mixture was slowly added dropwise to the isocyanate base oil mixture. After the addition was complete, the mixture was gradually heated to 165°C and kept at this temperature for 30 min to allow TDI and di-n-octylamine to react in situ in PAO8 base oil to generate urea molecules. After the reaction was complete, the system was naturally cooled to 20–25°C to obtain a urea dispersion with a mass fraction of 10 wt%. The obtained urea dispersion was a pale yellow transparent liquid, with no obvious flocculent precipitation observed, and the system had good fluidity. Side and top view photographs of the obtained sample are shown below. Figure 1 As shown in c and g.
[0058] Comparative Example 1: 2 wt% urea + 1 wt% micron-sized molybdenum disulfide / PAO8 dispersion
[0059] a. Preparation of urea-based dispersion: Weigh 0.106 g of toluene-2,4-diisocyanate (TDI) and add it dropwise to 9.4 g of PAO8 base oil. Stir magnetically at 45°C for 10 min to obtain a uniformly dispersed isocyanate base oil mixture. Separately weigh 0.294 g of di-n-octylamine (molar ratio of TDI to di-n-octylamine is 1:2) and add it to 10.0 g of PAO8. Stir at 40°C for 10 min to ensure uniform dispersion, obtaining an amine base oil mixture. Subsequently, slowly add the amine base oil mixture dropwise to the isocyanate base oil mixture. Under stirring, heat the mixture to 180°C and maintain the temperature for 60 min. After the reaction, cool the system to 20-25°C to obtain a urea-based dispersion with a urea molecular content of 2 wt%.
[0060] b. Preparation of material dispersion: Weigh 0.20 g of micron-sized molybdenum disulfide (particle size approximately 15 μm), add it to the above urea-based dispersion, stir for 10 min, sonicate for 10 min, stir again for 10 min, and repeat sonication for 10 min to obtain the material dispersion. The only difference between this comparative example and the embodiment is that the molybdenum disulfide used is a micron-sized material. The dispersion results are as follows: Figure 3 As shown.
[0061] Comparative Example 2: 2 wt% urea + 0.5 wt% micron-sized graphene / PAO8 dispersion
[0062] a. Preparation of urea-based dispersion: The preparation steps of the urea-based dispersion are the same as step a in Comparative Example 1, resulting in a urea-based dispersion with a urea molecule content of 2 wt%.
[0063] b. Preparation of material dispersion: Weigh 0.10 g of micron-sized graphene (sheet diameter approximately 20 μm), add it to the above urea-based dispersion, stir for 10 min, sonicate for 10 min, stir again for 10 min, and repeat sonication for 10 min to obtain the material dispersion. The only difference between this comparative example and the embodiment is that the graphene used is a micron-sized material. The dispersion results are as follows... Figure 3 As shown.
[0064] Figure 1 This is a photograph of the appearance of a urea-based dispersion with a urea molecular weight of 5 wt%. Figure 1It was found that the urea-based dispersions prepared using PAO8 and PEB8 as base oils were both colorless or pale yellow and transparent to semi-transparent, without any flocculent precipitate, and exhibited good fluidity. Experiments showed that even when the urea molecular content reached 10 wt%, the dispersion system remained colorless or pale yellow and transparent to semi-transparent, without the appearance of white flocculent precipitate. These results indicate that the urea-based compounds prepared in this invention have excellent oil solubility in base oils, undergo only limited intermolecular self-assembly, and essentially do not exhibit the thickening effect of traditional urea thickeners, which is significantly different from the formation of white flocculent precipitate in the oil phase by traditional urea thickeners.
[0065] The samples obtained in Examples 1-3 and Comparative Examples 1-2 were placed in an environment of 20-25℃ and left to stand. The appearance of the samples was observed and photographed after 1, 2, 3, 5, 7, and 10 days of standing. The results are as follows: Figure 3 As shown. By Figure 3 It can be seen that the samples obtained in Examples 1-3 remained uniformly dispersed after standing for 10 days, without significant sedimentation or stratification. However, the sample of Comparative Example 1 (micron-sized molybdenum disulfide) showed significant sedimentation starting from the 2nd-3rd day of standing, with the upper liquid gradually becoming clear, and severe sedimentation and stratification by the 10th day. The sample of Comparative Example 2 (micron-sized graphene) showed obvious flocculation and sedimentation on the first day of standing. These results indicate that the urea-based dispersion of the present invention has excellent auxiliary dispersion and stabilization effects on nanoscale materials (particle size or sheet size not greater than 1 μm), but limited dispersion and stabilization effects on micron-sized particles. Therefore, the urea-based dispersion of the present invention is suitable for the dispersion and stabilization of nanomaterials in oil-phase media. Furthermore, after long-term standing observation, the samples with better dispersion stability in the examples could be stably stored at 20-25°C for more than 100 days without significant sedimentation or stratification. Figure 4 Furthermore, when the nanomaterial dispersion settles after long-term storage, it can be restored to a uniform dispersion state and reused simply by undergoing ultrasonic treatment again, further enhancing its practical application value.
[0066] Figure 6 Friction test results were obtained for PAO8 base oil and the sample prepared in Example 1 on an SRV friction testing machine. The experimental conditions were: load 100 N, temperature 25 °C, frequency 25 Hz, and stroke 1 mm. Under these conditions, the friction coefficient of the sample obtained in Example 1 remained at approximately 0.13 throughout the test. In contrast, the PAO8 base oil experienced a brief failure after approximately 150 s, after which its friction coefficient remained at a higher level of 0.25. Compared to the PAO8 base oil, the average friction coefficient of the sample obtained in Example 1 was reduced by 49.4%. Therefore, the dispersant proposed in this invention not only achieves long-term stable dispersion of nanomaterials, but the resulting carbon nanotube dispersion also exhibits excellent friction-reducing properties.
[0067] In summary, this invention generates urea molecules through a one-step in-situ addition reaction of toluene-2,4-diisocyanate and di-n-octylamine in base oil. These urea molecules do not undergo strong self-assembly in the oil phase, maintaining the system's transparency to translucency and good fluidity. Simultaneously, the urea molecules effectively inhibit the aggregation of nanomaterials, achieving long-term stable dispersion of nanomaterials in the oil phase medium. The preparation method of this invention is simple, low-cost, and environmentally friendly, requiring no complex surface chemical modification of the nanomaterials. It is applicable to various nanomaterials such as carbon nanotubes, graphene, molybdenum disulfide, and hexagonal boron nitride, as well as various base oils such as PAO8, PEB8, and industrial white oil. The resulting nanomaterial dispersion can be used as a lubricating oil additive dispersion system or a cutting fluid, demonstrating good versatility and engineering application value.
[0068] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made to the technical solutions of the present invention by those skilled in the art without departing from the spirit of the present invention should fall within the protection scope of the present invention.
Claims
1. A urea compound, characterized in that, The urea compound has the structural formula shown in formula (Ⅰ): 。 2. A method for preparing a urea-based dispersion, characterized in that, Includes the following steps: (1) Add toluene-2,4-diisocyanate to the first part of the base oil, stir and disperse evenly to obtain an isocyanate base oil mixture; (2) Add di-n-octylamine to the second part of the base oil, stir and disperse evenly to obtain an amine base oil mixture; the molar ratio of toluene-2,4-diisocyanate to di-n-octylamine is 1:1.8~2.2; (3) The amine base oil mixture is added dropwise to the isocyanate base oil mixture, and the temperature is raised to 150~200℃ under stirring and kept at a constant temperature for 30~60 min, so that toluene-2,4-diisocyanate and di-n-octylamine react in situ in the base oil to generate urea molecules as shown in formula (I), and a urea-based dispersion is prepared. The mass percentage of urea molecules in the obtained urea-based dispersion is 2-10 wt%. The base oil is any one of polyalphaolefin, pentaerythritol tetra(2-ethylhexanoate), or industrial white oil.
3. The preparation method according to claim 2, characterized in that, The base oil is any one of polyalphaolefin or pentaerythritol tetra(2-ethylhexanoate).
4. The preparation method according to claim 2, characterized in that, The amount of toluene-2,4-diisocyanate used accounts for 0.66~1.66 wt% of the total mass of the reaction system, and the amount of di-n-octylamine used accounts for 1.33~3.33 wt% of the total mass of the reaction system.
5. The preparation method according to claim 2, characterized in that, The stirring and dispersion temperature in step (1) is 40~50℃ and the time is 10 min; the stirring and dispersion temperature in step (2) is 40℃ and the time is 10 min; in step (3), the temperature is raised to 170~180℃ and the reaction is kept at a constant temperature for 60 min.
6. The preparation method according to claim 2, characterized in that, The mass percentage of urea molecules in the obtained urea-based dispersion was 5 wt%.
7. A urea-based dispersion, characterized in that, It is prepared by the preparation method according to any one of claims 2 to 6.
8. A nanomaterial dispersion, characterized in that, It includes the urea-based dispersion of claim 7 and the nanomaterials dispersed in the urea-based dispersion.
9. The nanomaterial dispersion according to claim 8, characterized in that, The nanomaterial is at least one of carbon nanotubes, graphene, molybdenum disulfide, and hexagonal boron nitride, and its particle size or sheet size is no greater than 1 μm; the amount of the nanomaterial added accounts for 0.5 to 1 wt% of the total mass of the nanomaterial dispersion.
10. The application of the nanomaterial dispersion according to claim 8 or 9 as a lubricating oil additive dispersion system or a cutting fluid.